Glutathione reductase gsr-1 is an essential gene required for Caenorhabditis elegans early embryonic development - Mora-Lorca, José Antonio; Sáenz-Narciso, Beatriz; Gaffney, Christopher J.; Naranjo-Galindo, Francisco José; Pedrajas, José Rafael; Guerrero-Gómez, David; Agnieszka, Dobrzynska; Askjaer, Peter; Szewczyk, Nathaniel J.; Cabello, Juan; Miranda-Vizuete, Antonio (Elsevier, 2016)
Glutathione is the most abundant thiol in the vast majority of organisms and is maintained in its reduced form by the flavoenzyme glutathione reductase. In this work, we describe the genetic and functional analysis of the Caenorhabditis elegans gsr-1 gene that encodes the only glutathione reductase protein in this model organism. By using green fluorescent protein reporters we demonstrate that gsr-1 produces two GSR-1 isoforms, one located in the cytoplasm and one in the mitochondria. gsr-1 loss of function mutants display a fully penetrant embryonic lethal phenotype characterized by a progressive and robust cell division delay accompanied by an aberrant distribution of interphasic chromatin in the periphery of the cell nucleus. Maternally expressed GSR-1 is sufficient to support embryonic development but these animals are short-lived, sensitized to chemical stress and have increased mitochondrial fragmentation and lower mitochondrial DNA content. Furthermore, the embryonic lethality of gsr-1 worms is prevented by restoring GSR-1 activity in the cytoplasm but not in mitochondria. Given the fact that the thioredoxin redox systems are dispensable in C. elegans, our data support a prominent role of the glutathione reductase/glutathione pathway in maintaining redox homeostasis in the nematode.